Illustrated tales of Kusu Island - Peh, Yang Yu (2019)
Kusu Island is one of Singapore's sixty-three islands and has several names, such as "Pulau Tembakul" in Malay and "Peak Island" in English. Its most popular name, Kusu, comes from the Hokkien pronunciation of the Chinese characters 龟屿 (guī yǔ), which means 'Turtle Island'." As a small island city-state with centuries of history, Singapore is filled with traditional tales that have been passed down orally through generations. Kusu Island depicts two men – a Malay and a Chinese – who are saved by a giant turtle during a storm and then live on the island together. This island with the aid of the turtle is built through friendship and trust.